Enhancing Students' Motivation Using Gamification Methods in Fluid Mechanics Subjects - Razali, Nizamuddin; Muhamad Haris , Nurul Awatif; Rahim, Mohd Bekri; Yunus, Faizal Amin Nur; Abdul Rahman, Khairul Anuar; Ismail, Mohd Erfy (Research and Innovation in Technical and Vocational Education and Training, 2021)
In the 21st century, learning is now a technology that enhances students' understanding and contributes to teaching and learning. In helping the government build 21st Century Education (PAK 21), this study was aimed to identify the level of motivation by using gamification methods in fluid mechanics subjects. This study used a quantitative research method through a survey using questionnaires as the instrument to get the data and information for answering the research questions. A total of 113 students, including students from three (3) Vocational Education Bachelor Degree courses, were selected based on a purposive sampling method to complete the questionnaire survey given. The data were analyzed using the Statistical Package for Social Science (SPSS) version 26.0. During data analysis, the descriptive measurement was conducted, and one-way ANOVA was used to analyze the level of intrinsic & extrinsic motivation among students and the differences in motivation level across the field of study. Besides, the validity was made to ensure the questionnaire can be used. Content validity, face validity, and construct validity were used in this study to make sure the instrument's validity. Moreover, the pilot study was carried out to obtain the reliability of the questionnaire. Based on the analysis that has been made, Alpha Cronbach's value was 0.84 categorized as a high level. The results showed that the mean scores were high in terms of intrinsic motivation (mean = 4.24) and extrinsic motivation level (mean = 4.43) after using the gamification method. The results of the one-way ANOVA test inference analysis were not significant, with F (2,110) = 3.048, p = 0.051> 0.05 for intrinsic motivation level across the study area. For extrinsic motivation across the study, one-way ANOVA test results were not significant, with F (2,110) = 0.414, p = 0.662> 0.05. Therefore, this study has a positive impact and demonstrates that gamification methods can improve students' motivation level.